Genetic Templates and Coded Worlds: David Hontiveros’ Seroks Iteration 1: Mirror Man as World-Driven Dystopia - Guerrero, Sydney Paige (SARE: Southeast Asian Review of English, 2021)
In 2012, David Hontiveros revisited and expanded the world of his Carlos Palanca Memorial Award-winning short story, “Kaming Mga Seroks”, in Seroks Iteration 1: Mirror Man, which is set in a dystopic future where cloning is a booming industry, and genetic templates are pirated to create seroks or clones of clones. Mirror Man employs a fragmented style of storytelling that crafts a long-form narrative that is neither plot nor character-driven but world-driven. Through a mix of interviews, messages, recordings, and more, Mirror Man delves deeper into the world’s history and current events than it does into the lives of its recurring characters. In this way, the world of Seroks is not so much a backdrop against which the story takes place but the story’s main draw as it utilizes its dystopic setting to critique Philippine society, thus prompting the reader to reconsider the trajectory of the Philippines and reimagine its future.